Characteristics of the Home Industry inLambusa Village, Konda District, South Konawe Regency - Muslihun Husuni, La Ode Muhammad; Herdhiansyah, Dhian; Syukri, Muhammad; Asriani, Asriani (Tekper : Jurnal Teknologi dan Manajemen Industri Pertanian, 2023)
Abstract This research aims to determine the characteristics of the household tofu industry (home industry) in Lambusa Village, Konda District, South Konawe Regency. The research was conducted in July–August 2020 at Lambusa Village, Konda District, South Konawe Regency. Determining the research location was carried out using purposive sampling with the consideration that the majority of the population in the area meets their living needs from agricultural products, and the most abundant industry is tofu. This research uses a descriptive approach that is intended to describe, describe, and describe in depth the characteristics of the home industry. The research results show that the amount of tofu production is 24,204 kg and can produce tofu an average of 10,600 kg/month. Tools used in tofu processing include grinding machines, basins, sieves, tofu molds, plastic drums, baskets, furnaces, and zinc drums. The raw materials used in making tofu are soybeans, vinegar, and fuel. Industrial businesses sell tofu at the same price, namely Rp 7,500/kg. One kilogram of tofu consists of 40 pieces, with the size of each piece of tofu being 5 cm x 5 cm with a thickness of 2 cm. The weight of each piece of tofu is one ounce.